The underestimated posterior lymphatic drainage of the prostate: An historical overview and preliminary anatomical study on cadaver. Issue 2 (20th November 2019) - Boscolo‐Berto, Rafael; Siracusano, Salvatore; Porzionato, Andrea; Polguj, Michał; Porcaro, Antonio Benito; Stecco, Carla; Macchi, Veronica; De Caro, Raffaele
Abstract: Background: The evidence of pelvic lymph node metastases after radical prostatectomy (RP) with pelvic lymph node dissection (PLND) is one of the strongest prognostic factors for poor oncologic outcome. The extent of PLND, although representing a crucial step in RP, is still controversial. Currently, there is a critical drawback in clinical practice due to the lack of congruence between the known lymphatic drainage and cancer dissemination despite defined management by a surgical approach. We hypothesized the existence of alternative pathways for the lymphatic drainage of the prostate currently not considered in clinical daily practice. Methods: We carried out a literature review of the anatomic description of nodal drainage of prostate reported by online databases (MEDLINE/PubMed, EBSCO, Web of Science, Ovid, and Scopus) and the original texts since the 18th century, with an additional anatomical dissection on a human cadaver to confirm theoretical data. Results: The anatomical dissection study converged with the historical anatomical treatises in describing three groups of lymphatics devoted to carrying out prostatic nodal drainage. Apart from the ascending ducts from the cranial gland leading to the external iliac nodes; the lateral ducts leading to the hypogastric nodes; small lymphatic vessels from the posterior surface of the prostate, directed to the pararectal lymphatic plexus, in the direction of the lateral sacral lymph nodes and those at the sacral promontory (ie, pararectal and presacral lymph nodes) were observed. Conclusions: Our preliminary findings demonstrate that lymphatic drainage of the prostate extends beyond standard nodal templates actually considered in surgical daily practice, despite the knowledge reported by historical anatomical treatises. Further anatomical and experimental evidence are needed to investigate anatomical variability in humans, as well as to add more topographical details.